Paper 51: Multiple Prior Dislocations Lead to Poorer Outcomes of Isolated Medial Patellofemoral Ligament Reconstruction: A Retrospective Chart Review. Issue 7 (30th July 2022) - Ryskamp, David; Gonzalez, Roberto; Cavendish, Parker; Milliron, Eric; Dibartola, Alex; Duerr, Robert; Kaeding, Christopher; Flanigan, David; Magnussen, Robert; Meeks, Brett
Objectives: Patellar dislocation is a common knee injury and up to 35% who dislocate can develop recurrent patellar instability. In the setting of recurrent instability, medial patellofemoral ligament reconstruction (MPFLR) often restores knee stability. There has been recent interest in the evaluation of patient and surgical factors that may influence the outcomes of isolated MPFLR. Much of the previous work has focused on influences of anatomical measures; however, patient and injury characteristics may also impact surgical outcomes. We hypothesize that patients who suffer > 2 patellar dislocations prior to MPFLR will demonstrate poorer patient-reported outcomes (PROs) than those who experience ≤ 2 prior dislocations. Methods: Records were reviewed to identify patients who underwent MPFLR at a single academic institution in the United States between 2008 and 2016. Patients were excluded if they underwent concomitant tibial tubercle osteotomy or fixation of an osteochondral fracture. Patient demographics (age, sex, BMI), number of prior patellar dislocations, and patient anatomical measures (Caton-Deschamps index, tibial tubercle-trochlear groove distance, and trochlear sulcus angle) were collected. PROs were assessed with Norwich Patellar Instability (NPI) score, Knee injury and Osteoarthritis Outcome Score (KOOS), and Marx activity score. Outcomes of those with > 2 or ≤ 2 patellar dislocations were compared using linear regression analysis. Results: A total of 160 patients were identified who underwent isolated MPFLR. Ninety-five patients (60%) were available to complete PROs at a mean follow-up of 4.8 years post-operation. Patients with< 2 dislocations were younger (≤ 2 dislocations: 20.7 ± 9.4yrs, > 2 dislocations: 27.4 ± 9.4yrs; p < 0.001), though there were no other differences between groups in terms of demographics or radiographic anatomical measures (Table 1). Controlling for age, sex, BMI, and anatomical factors linear regression analysis found that patients with > 2 dislocations had lower KOOS pain (p = 0.003), ADLs (p = 0.025), Sports/rec (p = 0.009), and knee related QOL (p = 0.008) subscales (Table 2). Conclusions: Patients who suffer > 2 patellar dislocations prior to MPFLR demonstrate poorer PROs at 4.8 years post-operation than those who suffer < 2 dislocations prior to surgery. To our knowledge, no other study has investigated the relationship between the number of pior patellar dislocations and outcomes following MPFLR. Our findings emphasize the role patient and injury factors may play in determining outcomes following MPFLR. Table 1. Comparison of patients based on number of prior dislocations controlling for age, sex, BMI, CDI, TT-TG distance, and sulcus angle Table 2. PROs for patients with ≤ 2 or > 2 patellar dislocations prior to MPFLR, controlling for age, sex, BMI, CDI, TT-TG distance, and sulcus angle